ANALISIS KOMPETENSI GURU DALAM PERSPEKTIF ISLAM DAN PERMENDIKNAS - Muhtadin, Muhammad Akhsanul; Laksono, Tio Ari (TA'LIM : Jurnal Studi Pendidikan Islam, 2023)
The main problem of education in Indonesia lies in the quality of teachers at various levels of education. Teachers need to have good qualifications in conducting learning so that they become qualified. It is not wrong to say that quality students, both academically, expertise, emotional maturity and spiritual morality are in the hands of the teacher. To make this happen, teachers who have qualifications, competence, and high dedication in carrying out their duties in the world of education. In this study, researchers used library research methods or library research, namely research aimed at collecting data and information on various types of material contained in books or libraries. Various problems related to teachers are basically caused by a lack of mastery of competence so that teachers are not optimal in carrying out learning in class and outside the classroom. Competency standards issued by the ministry of education are designed to align teacher perceptions with the expectation that teachers in Indonesia will all have above average competence.